Ferroelectricity‐Driven Self‐Powered Ultraviolet Photodetection with Strong Polarization Sensitivity in a Two‐Dimensional Halide Hybrid Perovskite - Ji, Chengmin; Dey, Dhananjay; Peng, Yu; Liu, Xitao; Li, Lina; Luo, Junhua (Angewandte Chemie International Edition, 2020)
Polarization‐sensitive ultraviolet (UV) photodetection is highly indispensable in military and civilian applications and has been demonstrated with various wide‐band photodetectors. However, it still remains elusive to achieve the self‐powered devices, which can be operated in the absence of external bias. Herein, for the first time, ferroelectricity‐driven self‐powered photodetection towards polarized UV light was successfully demonstrated in a 2D wide‐band gap hybrid ferroelectric (BPA)2PbBr4 (BPA=3‐bromopropylammonium) (1). We found that the prominent spontaneous polarization in 1 results in a bulk photovoltaic effect (BPVE) of 0.85 V, that independently drives photoexcited carriers separation and transport and thus supports self‐powered ability. This self‐powered detector shows strong polarization sensitivity to linearly polarized UV illumination with a polarization ratio up to 6.8, which is superior to that of previously reported UV‐polarized photodetectors (ZnO, GaN, and GeS2). A ferroelectricity‐driven self‐powered ultraviolet photodetector employing a 2D hybrid perovskite ferroelectric (BPA)2PbBr4 (BPA=3‐bromopropylammonium) is presented. It shows strong polarization sensitivity, with a large polarization ratio of up to 6.8.